Pengaruh Kombinasi Probiotik Komersial Dan Bahan Herbal Terhadap Volume Flok dan Pertumbuhan Ikan Nila (Oreochromis niloticus) - Nursyahran, Nursyahran; Ramadhani, Arda; Mulyawan, Ardi Eko (Jurnal Riset Diwa Bahari (JRDB), 2024)
Biofloc technique is a cultivation method that utilizes microorganisms, especially heterotrophic bacteria, to convert toxic inorganic nitrogen waste, such as ammonia, into biomass that is beneficial for fish. In the biofloc system, heterotrophic bacteria play an important role in the formation of flocs, which are aggregates of microorganisms and organic particles that function as additional food sources for fish. These bacteria use nitrogen from ammonia in water to produce biomass, which can then be eaten by fish. This study aims to examine the effect of a combination of commercial probiotics and herbal ingredients on the growth of tilapia (Oreochromis niloticus). The method used in this study was an experiment with a Completely Randomized Design (CRD) consisting of four treatments and three replications. The treatments tested included treatment A (control), treatment B (EM4 + Ginger), treatment C (EM4 + Kencur), and treatment D (EM4 + Turmeric). This study was conducted for 35 days at the Moncongloe Maros Aquaculture Institute, with test fish in the form of tilapia seeds measuring 5-7 cm and aged 1 month. The results showed that the combination of commercial probiotics and herbal ingredients in treatment C (Probiotic EM4 + Kencur) produced the highest floc volume of 20.17 mL, while treatment D (EM4 + Turmeric) produced the lowest floc volume of 12.04 mL. Treatment C also recorded the highest Specific Growth Rate (SGR), which was 2.90%, while treatment D recorded the lowest SGR of 2.41%. Kencur is considered to have a positive effect because of its essential oil content which functions as a sedative effect, helps fish physiology, increases growth, maximizes protein digestibility, and increases feed efficiency. Anova analysis showed that SGR had a significant effect (P<0.05), while absolute length growth and survival rate did not show significant differences between treatments (P>0.05).